Precision cut lung slices as test system for candidate therapeutics in organophosphate poisoning. (15th August 2017) - Herbert, Julia; Thiermann, Horst; Worek, Franz; Wille, Timo
Highlights: ACh induced spontaneously reversible airway contractions in non-poisoned PCLS. In OP poisoned PCLS, ACh-induced airway contractions were irreversible. Atropine efficiently antagonized the irreversible airway contractions. The ability to counteract irreversible airway contractions shows the therapeutic potential of test compounds. PCLS are a robust test system to evaluate candidate therapeutics in OP poisoning. Abstract: Standard therapeutic options in organophosphate (OP) poisoning are limited to the administration of atropine and oximes, a regimen often lacking in efficacy and applicability. Treatment alternatives are needed, preferably covering a broad spectrum of OP intoxications. Although recent research yielded several promising compounds, e.g. bioscavengers, modulators of the muscarinic acetylcholine (ACh) receptor or bispyridinium non-oximes, these substances still need further evaluation, especially regarding effects on the potentially lethal respiratory symptoms of OP poisoning. Aim of this study was the development of an applicable and easy method to test the therapeutic efficiency of such substances. For this purpose, airway responsiveness in viable precision cut lung slices (PCLS) from rats was analysed. We showed that ACh-induced airway contractions were spontaneously reversible in non-poisoned PCLS, whereas in OP poisoned PCLS, contractions were irreversible. This effect could be antagonized by addition of the standard therapeutic atropine, thereby presenting a clear indication for treatment efficiency. Now, candidate therapeutic compounds can be evaluated, based on their ability to counteract the irreversible airway contraction in OP poisoned PCLS.